Determination of trace elements in some copper minerals by k0-neutron activation analysis - Taseska, M; Jaćimović, R; Stibilj, V; Stafilov, T; Makreski, P; Jovanovski, G (Elsevier BV, 2012)
Trace element contents in two copper minerals [brochantite [Cu(4)SO(4)(OH)(6)] and native Cu] using k(0)-NAA were determined before and after quantitative removal of copper. The distribution of 44 elements in the studied minerals was investigated. An important advantage of the proposed method is the possibility to determine the content of several elements (Al, Dy, Mg, Mn and V) via their short-lived nuclides after the electrolytic removal of Cu due to the elimination of matrix interferences.